Elastic and mechanical properties of cubic diamond and silicon using density functional theory and the random phase approximation. (February 2021) - Barhoumi, M.; Rocca, D.; Said, M.; Lebègue, S.
Abstract: The elastic constants play a central role in the regulation of the thermo-mechanical and anisotropic response of materials. Nevertheless, there is still a lack of theoretical and experimental data on these constants which limits the possibility of developing new materials with targeted mechanical responses. The elastic constants of diamond and silicon as second and third-order are obtained using density functional theory (LDA, GGA, and HSE) and for the first time with the adiabatic-connection fluctuation–dissipation theorem in the random phase approximation. Our SOECs calculations show an excellent agreement with experimental data. In this framework, we study the mechanical properties such as Young's modulus, Poisson's ratio, bulk modulus, and shear modulus of diamond and silicon structures. Also, we visualize the 3D plot, as well as 2D for Young's modulus, Poisson's ratio, and others. For the TOECs, we show that can be taken our RPA results as a reference, since there is still a lack of reliable previous theoretical and experimental data of these materials. Highlights: We study the SOEC and TOEC of Si and C. We show that can be taken our RPA results as a reference. Young's modulus and Poisson's ratio are fully described. We visualize the 3D plot, as well as 2D for Young's modulus and Poisson's ratio.